2021
DOI: 10.1007/s10758-021-09533-2
|View full text |Cite
|
Sign up to set email alerts
|

University Virtual Learning in Covid Times

Abstract: Online training is demanded in the ubiquitous society we live in, and this is especially true if we consider the current situation at universities due to the Government issuing a state of alarm decree which requests all citizens to remain at home. The goal of this study is to determine the opinion of university students from different Spanish campuses on e-learning platforms, by the means of a descriptive and correlational study design, with N = 431. The results reveal that there is still a long road ahead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…A vital aspect of virtual learning is the teachers and instructors who prepare and deliver the online learning materials. Marín-Díaz et al, ( 2021 ) noted that students viewed the instructor’s role as one primarily of guidance and evaluation of completed work. Tang et al, ( 2020 ) also found that students placed communication with the teacher as highly important and were dissatisfied with virtual learning when there was poor communication.…”
Section: Vc Learning In Uaementioning
confidence: 99%
See 3 more Smart Citations
“…A vital aspect of virtual learning is the teachers and instructors who prepare and deliver the online learning materials. Marín-Díaz et al, ( 2021 ) noted that students viewed the instructor’s role as one primarily of guidance and evaluation of completed work. Tang et al, ( 2020 ) also found that students placed communication with the teacher as highly important and were dissatisfied with virtual learning when there was poor communication.…”
Section: Vc Learning In Uaementioning
confidence: 99%
“…The convenience to work at the time and place of the student choice is very valuable when undertaking virtual learning (Marín-Díaz et al, 2021 ). VC learning was seen by students as being very convenient (Hande, 2014 ).…”
Section: Vc Learning In Uaementioning
confidence: 99%
See 2 more Smart Citations
“…This can be due to the balance between online and face-to-face learning. In online learning, teachers can use various learning media and with face-to-face learning students and teachers can interact directly for material that is not understood when online learning (Di Giacomo & Di Paolo, 2021;Marín-Díaz et al, 2021;Torda & Shulruf, 2021). In PJHS Z, full online learning has the highest percentage where many data sources use full online learning.…”
Section: Discussionmentioning
confidence: 99%